Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1469-0691.2002.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre assessment of linezolid antimicrobial activity and spectrum in Europe: report from the Zyvox® antimicrobial potency study (ZAPS-Europe)

Abstract: Compared to the North American component of this study, there was substantially less vancomycin resistance among E. faecium isolates (Europe 3.0% vs. North America 63.4%). While the occurrence of penicillin-resistant S. pneumoniae in Europe and North America was similar (25.1% vs. 29.7%), the recovery of high-level penicillin-resistant strains was nearly three-fold higher in North America (4.9% vs. 13.2%). Only linezolid was universally active against all the tested Gram-positive isolates at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…Table 2 provides a summary of the organisms tested against linezolid and the comparator antimicrobial agents. The activity of linezolid against staphylococci proved to be exceptional in 2003 and nearly identical to that found in the 2002 ZAAPS Program (Table 3) [13] and the pre-marketing ZAPS data [14][15][16][17][18]. The linezolid MIC 90 and modal MIC for S. aureus and CoNS were 2 and 1 mg/L, respectively, with all isolates categorised as susceptible [20].…”
Section: Antimicrobial Usagementioning
confidence: 60%
See 2 more Smart Citations
“…Table 2 provides a summary of the organisms tested against linezolid and the comparator antimicrobial agents. The activity of linezolid against staphylococci proved to be exceptional in 2003 and nearly identical to that found in the 2002 ZAAPS Program (Table 3) [13] and the pre-marketing ZAPS data [14][15][16][17][18]. The linezolid MIC 90 and modal MIC for S. aureus and CoNS were 2 and 1 mg/L, respectively, with all isolates categorised as susceptible [20].…”
Section: Antimicrobial Usagementioning
confidence: 60%
“…and CoNS isolates were two-fold lower (MIC 90 , 1 mg/L) than either S. aureus or the enterococci MIC 90 (2 mg/L). This relationship has not changed from the initial pre-marketing surveillance efforts performed for this oxazolidinone [12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest, linezolid exhibited excellent activity against DRSP, S. pyogenes, S. agalactiae, and viridans group streptococci. Other linezolid surveillance studies have consistently demonstrated similar activity [4,[10][11][12][13][14][15][16][17][18], including several from Europe [14][15][16][17]. While among Gram-positive organism infections vancomycin may still be a preferred drug for treatment, emerging resistance in enterococci and S. aureus has seriously compromised this agent in some geographic regions.…”
Section: Discussionmentioning
confidence: 95%
“…In the laboratory, strains of linezolid-resistant enterococci have been generated by serial passage of clinical VRE isolates by using doubling dilutions of linezolid; linezolid resistance was associated with mutations in the domain V region of the 23S rRNA gene (21). Clinical infections by linezolid-resistant Enterococcus species have been reported at individual centers (2, 9, 11, 13) but have been rare in the United States and internationally (3,4,6). The true frequency of linezolid-resistant enterococcal infections may be underestimated, because many laboratories do not routinely test enterococccal isolates for linezolid susceptibility.…”
Section: Case Reportmentioning
confidence: 99%